2007
DOI: 10.1155/2007/257602
|View full text |Cite
|
Sign up to set email alerts
|

Markers of Angiogenesis in Ovarian Cancer

Abstract: Tumor development and progression are inherently dependent on the process of angiogenesis. Recently, anti-angiogenic therapy has started to show promise as an effective treatment strategy in many solid tumors including ovarian carcinoma. Unfortunately, lack of effective biomarkers presents a challenge for oncologists in treatment planning as well as monitoring response of new anti-vascular agents. Previously, quantification of angiogenesis by microvessel density analysis provided useful prognostic information,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 110 publications
(124 reference statements)
0
12
0
Order By: Relevance
“…In contrast, another study found that the MVD from the primary ovarian tumors (assessed by vWF and CD31) was independently related to poorer outcomes in early stage (I and II) patients, but not in advanced stage (III and IV) patients [9]. A summary of these and other studies examining the correlation of MVD with disease characteristics and outcome can be found in a review by Merritt and Sood [10].…”
Section: Angiogenesis In Ovarian Cancermentioning
confidence: 99%
“…In contrast, another study found that the MVD from the primary ovarian tumors (assessed by vWF and CD31) was independently related to poorer outcomes in early stage (I and II) patients, but not in advanced stage (III and IV) patients [9]. A summary of these and other studies examining the correlation of MVD with disease characteristics and outcome can be found in a review by Merritt and Sood [10].…”
Section: Angiogenesis In Ovarian Cancermentioning
confidence: 99%
“…Bamberger and Perret in 2002 concluded that in contrast with the breast tumor evaluation, there is no clear correlation of the MVD parameter with an ovarian cancer patient age, tumor stage, growth rate, dimension, ascites; for the various histological subtypes of ovarian cancer, MVD is different [1]. The further research in this direction elucidated the similar contradictions [74]. It can be hypothesized that the discrepancy of various conclusions is explained by the heterogeneity of patients genotypes in context of the biomarker expression.…”
Section: The Concepts Of the Automated Cancer Diagnosis And The Assesmentioning
confidence: 99%
“…58 Although IL-6-mediated tumor growth and angiogenesis has been demonstrated in ovarian cancer models, 59 the benefit of IL-6 as a marker of ovarian tumor angiogenesis remains to be determined. 52 …”
Section: Novel Biomarker Development In Eocmentioning
confidence: 99%